The effect of medicinal plants in the treatment of sexual disorders: A narrative Review - Maryam Farahmand; Fahimeh Ramezani Tehrani (Mashhad University of Medical Sciences, 2021)
Introduction: One of the most important factors affecting the stability of marital life is sexual health, which affects the human's quality of life. Therefore, it is important to take appropriate measures to maintain sexual health and prevent and treat the sexual disorders. This study was performed with aim to review the effect of medicinal plants in the treatment of sexual disorders. Methods: To find the related articles in this narrative review study, the related keywords were searched in the databases of PubMed, Scopus, Web of Science, SID, Magiran, Embaseand Google Scholar until March 2020 without time limitation. For each plant, the selected clinical trials and reviews with full text and published in English or Persian were used. Results: In the present review study, after an initial review of 717 articles, finally 75 articles were reviewed.According to the findings of this study, the effects of plants on sexual disorders are different. Some plants like as Rose reduce dyspareunia, create orgasm and increase libido and some plants such as Ginger improve erectile dysfunction and sexual satisfaction. Some plants like as Tribulus are effective in reducing sexual dysfunction by increasing the number and quality of sperm as well as the increasing testosterone hormone. Conclusion: The findings of this study showed that the use of appropriate plants can be effective in treating sexual disorders; however, more studies in this field are needed.